Africa : tradition and change - Rich, Evelyn Jones; Wallerstein, Immanuel Maurice, 1930- (New York : Random House School Division, 1972)
This textbook discusses not only the history of the African continent and its varied peoples but also the cultures and civilizations, the European intrusion, slave trade, colonialism, and the black image of both America and Africa.
Includes bibliographical references.
Keywords: Africa -- History; Africa -- History